Recombinant Thrombomodulin and Activated Protein C in the Treatment of Disseminated Intravascular Coagulation - Maruyama, Ikuro (Thrombosis and Haemostasis, 1999)
The blood coagulation cascade is regulated by the luminal surface of the endothelial cell lining.1 Endothelial cells synthesize tissue factor pathway inhibitor (TFPI), which, in part, binds to the cell surface glycosaminoglycans and inhibits factors Xa, VIIa, and tissue factor.2 Endothelial cells also produce and exhibit thrombomodulin (TM) on their luminal surface.3 TM is a kind of thrombin receptor that forms a 1:1 complex with thrombin. In this complex, thrombin activates protein C (PC) more than 1,000-fold more than thrombin alone. TM then loses its procoagulant activities, which include fibrinogen clotting, activation of factors V and VIII, and platelet activation. Thus, TM converts thrombin from a procoagulant protease to an anticoagulant. Pathologic states, such as an endothelial injury or perturbation or continuous rapid coagulation cascade activation, overcomes the endothelial regulating activity, resulting in the development of intravascular coagulation and the induction of disseminated intravascular coagulation (DIC). Theoretically, then, supplementing soluble TM or activated PC (APC) to reconstitute the endothelial coagulation regulation system in the circulation and regulate pathologically-activated blood coagulation could be beneficial. In this chapter, application of soluble TM and APC in the treatment of DIC is reviewed.